2022
DOI: 10.1093/hr/uhab013
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting effects of genotype and root size on the fungal and bacterial communities associated with apple rootstocks

Abstract: The endophytic microbiome of plants is believed to have a significant impact on its physiology and disease resistance, however, the role of host genotype in determining the composition of the endophytic microbiome of apple root systems remains an open question that has important implications for defining breeding objectives. In the current study, the bacterial and fungal microbiota associated with four different apple rootstocks planted in April, 2018 in the same soil environment and harvested in May, 2019 wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…On the other hand, several works show that host genotypes affect root endophyte cooccurrence networks [70,[112][113][114]. In our study, we observed that the root-associated AMF network was less dense in 1103 P rootstock than in R 110.…”
Section: Land Use Soil Type and Rootstock Effects On Culturable Amf C...contrasting
confidence: 43%
“…On the other hand, several works show that host genotypes affect root endophyte cooccurrence networks [70,[112][113][114]. In our study, we observed that the root-associated AMF network was less dense in 1103 P rootstock than in R 110.…”
Section: Land Use Soil Type and Rootstock Effects On Culturable Amf C...contrasting
confidence: 43%
“…Though root order data were not collected in this study, the relationship between root diameter and root function of apple roots has been elucidated [20]. The relationship between root diameter and function provides a compelling argument that a 2 mm diameter cutoff for classifying absorptive roots in apple overestimates this population due to inclusion of structural roots, despite its common use in the literature [16][17][18]. Thus, in the present study, only roots with diameters ≤ 0.4 mm were classified as absorptive based on [20].…”
Section: Discussionmentioning
confidence: 94%
“…Fine roots of tree species are relatively short-lived (i.e., several months) and account for most of the total root length [12,13]. Fine, non-woody roots with diameters < 2 mm are generally associated with nutrient and water acquisition for a range of species [14,15], including apple [16][17][18]. More recently, studies on root function argue that a 2 mm cutoff is non-discriminative for segregating absorptive from structural or pioneer roots and, thus, highly overestimates the actual percentage of absorptive roots [19].…”
Section: Introductionmentioning
confidence: 99%
“…In grafted plants, root associated microbiota composition can be responsive to rootstock genotypes, 30 , 31 but the existence of interaction between scion and rootstock in the root microbiota recruitment is often neglected. Recent studies on grafted grapevine plants have however shown the effect of both scion and rootstock on the rhizosphere composition.…”
Section: Discussionmentioning
confidence: 99%